2019
DOI: 10.5688/ajpe6875
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacy School Characteristics on NAPLEX First-time Pass Rates

Abstract: Objective. To assess the impact of pharmacy school characteristics on the pass rates of students taking the North American Pharmacist Licensure Examination (NAPLEX) for the first time. Methods. A retrospective review of NAPLEX first-time pass rates, pharmacy school characteristics and percent of total graduating class who matched for a first postgraduate year (PGY1) residency was performed for 2014, 2015, and 2016. All US colleges of pharmacy accredited as of July 2017 were included. Independent samples t test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 12 publications
(17 reference statements)
1
29
0
Order By: Relevance
“…15 Williams et al compared mean NAPLEX pass rates between various categories of schools from 2014 through 2016. 16 These studies distinguished four risk factors, based on the potential for perceived value by prospective applicants.…”
Section: Ramifications For Programs and Facultymentioning
confidence: 99%
See 2 more Smart Citations
“…15 Williams et al compared mean NAPLEX pass rates between various categories of schools from 2014 through 2016. 16 These studies distinguished four risk factors, based on the potential for perceived value by prospective applicants.…”
Section: Ramifications For Programs and Facultymentioning
confidence: 99%
“…17 Williams et al reported higher NAPLEX pass rates for public schools than private (p<.001). 16 Figure 1 illustrates that public schools achieved a higher mean NAPLEX pass rate every year from 2008 through 2019, and the disparity between the two groups widened markedly after the exam was modified in 2016. 17 According to Ford's tuition: licensure index, the difference in value is statistically significant (p=.0001).…”
Section: Ramifications For Programs and Facultymentioning
confidence: 99%
See 1 more Smart Citation
“…2 While the growth of new and existing PharmD programs has done much to address previously projected pharmacist manpower shortages, it is now recognized that market opportunity for both academic institutions and newly licensed practitioners has plateaued if not slightly declined nationwide, [3][4][5] average PharmD program tuition has steadily increased disproportionate to pharmacist salaries, 6,7 and pass rates for the North American Pharmacist Licensure Examination (NAPLEX) have progressively declined since 2014. 8 Given this unique climate, many in the profession now advocate for a temporary moratorium on new program accreditation. 9 It therefore becomes essential that both prospective students and program leaders pay special attention to student tuition and successful pharmacist licensure, both of which are components of the program value index used in this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Though de novo, the TLI is not without some degree of controversy, much of which derives from the now-routine use of NAPLEX data as program outcomes. 8,[13][14][15][16] Popovich and colleagues 17 have raised important concerns in this regard, echoing remarks from officials at the National Association of Boards of Pharmacy (NABP) that "licensure examinations were never intended to measure education or pinpoint specific weaknesses in teaching, curriculum, or the program in the college of pharmacy." 11 Nevertheless, by requiring publication of licensure pass rates on program websites, ACPE clearly recognizes the importance of these metrics on program valuation.…”
Section: Introductionmentioning
confidence: 99%